Assessment of Teachers’ Competence and Interest in Online Teaching during the COVID-19 Pandemic in Nigeria - Sulaimon Adewale; Omotayo Adewale Awodiji; Simeon Oluniyi Ariyo (International Journal of Pedagogy and Teacher Education, 2022)
Despite the numerous advantages of the online mode of instruction in terms of flexible learning methods, convenience, broader coverage and its ability to ensure that no child was ignored educationally during the COVID-19 lockdown, teachers found it difficult to cope with such an approach. A survey was conducted on teachers' interests, competencies, and awareness of the online mode of instruction and its possible problems. The snowball sampling technique was used to identify 377 teachers at all levels of education in Nigeria during the lockdown. Amongst the outcomes of the study, it was revealed that teachers were fully competent in online teaching, thus encouraging them to continue using the approach after the COVID-19 pandemic. Support from private organisations, especially in the provision of subsidised technology devices and organisation of skills development programmes for teachers at all levels of education, will enhance their competency and performance in the ‘new normal’ generation.